Complex management of larger strangulated incisional hernia in a post-multiple abdominal surgery in a morbidly obese patient-a case report and surgical review - Verma, Sandeep; Vidit; Kataria, Gaurav; Chatterjee, Rituparna; Arora, Bhavinder K. (International Surgery Journal, 2024)
Strangulated incisional hernia following a post-hernia repair is a serious and potentially rare life challenging condition that can occur after surgical intervention. Incisional hernias accounts for 15-20% of all abdominal hernias which occur at the site of a previous surgical incision where the integrity of the fascia has not been fully restored. We are presenting a case report of a 49 years lady who came with complaints of abdominal swelling and pain abdomen following multiple abdominal surgeries diagnosed with strangulated incisional hernia following post hernia repair. It was managed by emergency surgical intervention that is removal of previously kept mesh and resection of gangrenous segment of bowel with end ileostomy after keeping overall patient’s condition.